Replacing the transit passage regime with freedom of navigation in the Strait of Malacca: A case study with special reference to the Korea Strait - Rusli M.H.B.M.; Mustafa M.B.; Wan Talaat W.I.A.B. (2024)
Indexed by WOS/ Scopus